1973
DOI: 10.1590/s0004-282x1973000100005
|View full text |Cite
|
Sign up to set email alerts
|

Síndrome de Melkersson-Rosenthal: relato de 4 casos e revisão da literatura

Abstract: A síndrome de Melkersson-Rosenthal consta de paralisia facial periférica, edema da face e língua plicata. Justifica-se a apresentação destes casos pela sua raridade pois encontramos apenas 52 casos registrados na literatura a nosso alcance, sendo que só 22 com a tríade completa.Melkersson

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Melkersson-Rosenthal syndrome (MRS) is a rare granulomatous neuro-mucocutaneous condition [ 1 ] characterized by the triad facial paralysis, ipsilateral facial edema, and fissured tongue. In 1928, Melkersson described the paralysis and facial edema, and 3 years later, Rosenthal observed that those symptoms were presented in outbreaks, and were frequently associated with fissured tongue [ 2 ]. Nevertheless, it was only in 1949 when the term ‘Melkersson-Rosenthal syndrome’ was used for the first time, by Luscher [ 3 ], [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Melkersson-Rosenthal syndrome (MRS) is a rare granulomatous neuro-mucocutaneous condition [ 1 ] characterized by the triad facial paralysis, ipsilateral facial edema, and fissured tongue. In 1928, Melkersson described the paralysis and facial edema, and 3 years later, Rosenthal observed that those symptoms were presented in outbreaks, and were frequently associated with fissured tongue [ 2 ]. Nevertheless, it was only in 1949 when the term ‘Melkersson-Rosenthal syndrome’ was used for the first time, by Luscher [ 3 ], [ 4 ].…”
Section: Discussionmentioning
confidence: 99%